2011
DOI: 10.1590/s0102-695x2011005000018
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like and sedative effects of Hydrocotyle umbellata L., Araliaceae, extract in mice

Abstract: Abstract:The plant Hydrocotyle umbellata L., Araliaceae (water pennywort), is widely used in Brazilian folk medicine to reduce anxiety. This work investigates the anxiolytic-like effects of the ethanol extract from H. umbellata subterraneous parts as well as the extract's other putative central nervous system effects that could justify its common use. Oral dosing of the extract (0.3 and 1 g/kg) clearly showed an anxiolytic-like profile in the elevated plus maze test where it increased the percentage of entries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Several plants inducing increasing exploration in open arms in the elevated plus-maze test are used to diminish anxiety in folk medicine. Among them Hydrocotyle umbellata (Rocha et al, 2011) and Aloysia polystachya (HellionIbarrola et al, 2005;Mora et al, 2005) were mentioned for South America. Furthermore, elevated plus-maze test is recognized as an useful tool to detect the effect of anxiolytic drugs (Hogg, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Several plants inducing increasing exploration in open arms in the elevated plus-maze test are used to diminish anxiety in folk medicine. Among them Hydrocotyle umbellata (Rocha et al, 2011) and Aloysia polystachya (HellionIbarrola et al, 2005;Mora et al, 2005) were mentioned for South America. Furthermore, elevated plus-maze test is recognized as an useful tool to detect the effect of anxiolytic drugs (Hogg, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Upon reviewing the literature, it was found that CA is reported to exhibit same therapeutic effects as these 30 contemporary drugs. CA manifests anti-diabetic (Rahman et al, 2011;Emran et al, 2015), anti-ulcer (Sairam et al, 2001;Abdulla et al, 2010), anti-fungal (Lalitha et al, 2013), anti-cholinergic (Arora et al, 2018), anti-cancer (Hamid et al, 2016;Ren et al, 2016), anti-bacterial (Arumugam et al, 2011;Idris and Nadzir, 2017), anxiolytic (Wijeweea et al, 2006;Wanasuntronwong et al, 2012), anti-convulsant (Manasa and Sachin, 2016; Sudha et al, 2002), anti-inflammatory (Somchit et al, 2004;Chippada et al, 2011), anti-diarrheal (George et al, 2009), anti-psychotic (Chimbalkar et al, 2015;Chen et al, 2003), anti-nociceptive (Somchit et al, 2004;George et al, 2008), analgesic (Saha et al, 2013;Qureshi et al, 2015) and sedative (Hossain et al, 2005;Rocha et al, 2011) properties. Though it has been proved that CA possesses the aforesaid properties in various studies, the specific compounds or the mechanism of action responsible for all these properties are not known.…”
Section: The Contemporary Medicinesmentioning
confidence: 99%
“…H. umbellata L. leaves in high doses produce emetic effects and are potentially toxic (Corrêa 1984, Reis et al 1992, Fischer et al 1994. Our previous study found that the ethanolic extract from H. umbellata L. showed anxiolytic-like and sedative effects in mice (Rocha et al 2011).…”
Section: Introductionmentioning
confidence: 95%